Entrepreneurship : determinants and policy in a European-US comparison - Audretsch, David B., 1954-; Thurik, Roy; Verheul, Ingrid; Wennekers, Sander; SpringerLink (online služba) (Boston, MA : Springer US, 2002)
Without a clear and organized view of where and how entrepreneurship manifests itself, policy makers have been left in uncharted waters without an analytical compass. The purpose of this book is to provide such an analytical compass for directing how public policy can shape and promote entrepreneurship. We do this in two ways. The first is to provide a framework for policymakers and scholars to understand what determines entrepreneurship. The second is to apply this framework to a series of cases, or country studies. In particular, this book seeks to answer three questions about entrepreneurship: What has happened over time? Why did it happen? And, what has been the role of government policy? The cornerstone of the book is the proposed Eclectic Theory of Entrepreneurship. The goal of the Eclectic Theory is to provide a unified framework for understanding and analyzing the determinants of entrepreneurship. The Eclectic Theory of entrepreneurship integrates the different strands from relevant fields into a unifying, coherent framework. At the heart of the Eclectic Theory is the integration of factors shaping the demand for entrepreneurship on the one hand, with those influencing the supply of entrepreneurs on the other hand. The key to understanding the role of public policy is through identifying those channels shifting either the demand for or the supply of entrepreneurship by policy instruments. The findings in this book show that, by utilizing the framework provided by the Eclectic Theory of Entrepreneurship, it is within the grasp of policymakers to identify the determinants of entrepreneurship in a particular country setting at a particular point in time. This will be essential in formulating new public policies to promote entrepreneurship and, ultimately, economic growth, job creation and international competitiveness.
Understanding Entrepreneurship Across Countries and Over Time -- An Eclectic Theory of Entrepreneurship: Policies, Institutions and Culture -- Determinants of Entrepreneurship in France -- Determinants of Entrepreneurship in the Netherlands -- Determinants of Entrepreneurship in Germany -- Determinants of Entrepreneurship in The United States of America.
Obsahuje bibliografii a rejstřík
Elektronická reprodukce.
Keywords: podnikání -- Evropa; podnikání -- Spojené státy americké; management; hospodářská politika -- Evropa; hospodářská politika -- Spojené státy americké; ekonomický růst -- Evropa; ekonomický růst -- Spojené státy americké; business -- Europe; business -- United States; management; economic policy -- Europe; economic policy -- United States; economic development -- Europe; economic development -- United States; kolektivní monografie; elektronické knihy; e-knihy online; collective monographs; electronic books; e-books online